Violência por parceiro íntimo na gestação : prevalência e fatores associados à saúde reprodutiva da mulher - Sgobero, Jenny Karol Gomes Sato (2013)
This was a descriptive, cross-sectional, quantitative study with the overall objective of investigating the prevalence of violence by an intimate partner against pregnant women and its link to women's reproductive health. A total of 358 recent mothers were interviewed, residing in Maringa and who had been admitted to the rooming-in unit of two hospitals that provide care through Brazil's Unified Health System (SUS), in the period between December 2012 and April 2013. A multidimensional research tool, validated in Brazil by Schraiber (2010), was used to evaluate women's health and domestic violence .The collected data were organized in an Excel 2007 spreadsheet. Descriptive analysis was carried out using Statistica 7 software. Epi Info 7 software was used for statistical analysis, and Chi-square was chosen as the association test, considering α=5%. Odds Ratio (OR)was used to measure the magnitude of the association between variables. Tests with p<0.05 were regarded as statistically significant. The results found were presented in two articles. The first one showed a prevalence of physical violence by an intimate partner during pregnancy and associated factors. The dependent variable was the occurrence of physical violence by an intimate partner during the same or previous pregnancies. An association was observed with socio-demographic and economic characteristics, as well as the mother's habits (age, education, having a partner, occupation, family income expressed as multiples of the minimum wage, race/color, religion, alcohol intake, smoking, drug use and number of pregnancies); obstetric and reproductive history (fetal death, abortion, premature children or children with low weight at birth, age of first sexual experience, refusal to use condoms, and children from another father); and the characteristics and habits of the partner (age, education, employment during pregnancy, whether he wanted the pregnancy, alcohol intake and drug use). It was detected that the prevalence of physical violence during pregnancy was 7.5% and that the variables with statistical significance were: number of pregnancies; religion; smoking by the mother during the pregnancy; having children from another partner; use of illicit drugs by the partner; and partner not employed during the pregnancy. In the second article, suffering violence in the last 12months before childbirth was the independent variable, and three different types of violence were measured: psychological, physical and sexual. To get to know the population of women who had complications during pregnancy, socio-demographic characteristics and mother habits were assessed. Affirmative answers for urinary tract infection, pregnancy hypertension, virginities, placental abruption, premature labor, , hyperemesis and amniorrhexis were regarded as clinical complications during pregnancy. It was observed that 55.3% of all interviewed women had some sort of clinical complication during pregnancy; of those, 20.2% suffered psychological violence;6.6% physical violence; 2.5% sexual violence; and 8.6% physical/sexual violence. The obstetric complications linked to violence were urinary tract infection and premature labor. The findings of this study showed that having multiple pregnancies, risk behaviors by the woman and partner, the unemployment situation of the partner and family rearrangements with children from another father were the factors that permeated the situation of physical violence by an intimate partner during pregnancy. Clinical complications during pregnancy were associated with physical and sexual violence. The repercussions of violence by an intimate partner on the woman's health and the obstetric complications this creates are still an object of study that must be further explored in academic studies and assistance practices.